An analytical analysis of mixed convective MHD casson flow with ramped wall temperature - Husna Izzati, Osman; Zulkhibri, Ismail; Nur Fatihah, Mod Omar; Vieru, Dumitru; Mahadzir, S; Sibaroni, Y.; Riauan, M. A. I (WSEAS, 2024)
This research discusses the behavior of magnetohydrodynamic Casson fluid subjected to a ramped wall temperature along an infinitely inclined plate. Non-Newtonian fluid, specifically the Casson fluid, is employed to characterize fluid behavior in this research. The effects of porous media, chemical reactions, and radiation are considered. In practical applications, non-Newtonian fluids find use in lubrication such as grease, engine oil, etc. The Laplace transform technique has been applied during this study where ordinary differential equations are converted from the governing partial differential equations with suitable boundary conditions. These transformed dimensionless equations are subsequently solved numerically with Mathematica, and we have achieved the exact solutions of momentum, followed by energy and finally concentration. In the results section, we have analyzed the behavior of flow features under varying conditions of key parameters, including the governing parameters, the unsteadiness parameter, and the Casson parameter. All the results are shown and analyzed in graphs.